PENDIDIKAN AQIDAH-AKHLAK DI ERA DIGITAL - Silviana Putri Kusumawati (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
The rapid development of the times has led to the emergence of a new era, which is popularly known as the digital era. The digital era is an era where everyone can easily access information throughThe rapid development of the times has led to the emergence of a new era, which is popularly known as the digital era. The digital era is an era where everyone can easily access information through digital networks. The existence of this digital era, affects various sectors of life, including the education sector. In the education sector, this digital era facilitates and accelerates the search for knowledge, information and communication. This certainly has a positive effect on the world of education. However, in addition to having a positive impact, the existence of this digital era also has negative impacts, including making humans as individual beings. Moral education is education that teaches a person's morals and morals. With the existence of akidah morals education, it makes people more active and moral in living life. In this period, of course, it is very important to have strong morals and good morals in order to be able to respond wisely to this digital era. This research is intended to determine the role of morals in the digital era. The results of the research were obtained from literature studies related to moral education in the digital era. In this study, the results show that moral education is able to make human beings wise in responding to the progress of the times, especially in this digital era.